Language Endangerment in South Asia (Patan Pragya, 2019)
Language endangerment is the very critical issues of 21st century because the extinction of each language results in the irrecoverable loss of unique expression of the human experience and the culture of the world. Every time a language dies, we have less evidence for understanding patterns in the structure and function of human languages, human prehistory and the maintenance of the world’s diverse ecosystems. Language is thus essential for the ability to express cultural knowledge, the preservation and further development of the culture. In the world, 500 languages are spoken by less than 100 peoples and 96% of the worlds languages are spoken only 4% of the world’s population. Data shows that all most all the minority languages of world are in endangered and critical situation and not becoming to the culture transmitter. This paper will explain the process, stages, paradigms, as well as the language endangerment in global and in South Asian context.